Calibration of the E and B EXperiment (EBEX), a balloon-borne cosmic microwave background polarimeter. - Polsgrove, Daniel Edward (2009)
University of Minnesota Ph.D. dissertation. October 2009. Major: Astrophysics. Advisor: Professor Terry J. Jones. 1 computer file (PDF); xiv, 150 pages, appendices A-B. Ill. (some col.) We discuss pre-flight calibration of the E and B EXperiment (EBEX), a balloon-borne telescope designed to measure the B-mode polarization anisotropy of the cosmic microwave background (CMB). EBEX will observe the sky with 8' resolution in each of three bands centered on 150, 250 and 410 GHz. Employing over 1,400 detectors and performing polarimetry through a continuously rotating half-wave plate with fixed wire-grid polarizer, we expect to detect the B-mode signal or set a new upper limit one order of magnitude below the current value. In this thesis we describe a set of ground-based experiments devised for calibrating instrumental response to incident millimeter-wave flux with varying spectral and polarization properties. We chronicle the design, construction and execution of these experiments, along with preliminary results from tests executed prior to our North American (NA) test flight which originated at the Columbia Scientific Ballooning Facility, Ft Sumner, NM in June 2009. A brief review of this inaugural flight is provided, as is a synopsis of our current plan for a comprehensive calibration strategy to be implemented in conjunction with a future long duration balloon (LDB) flight over Antarctica.